ON THE ENCAPSULATION OF THE NEW XLINDLEY DISTRIBUTION - Barrouk Bachir; Zeghdoudi Halim (JOURNAL OF MECHANICS OF CONTINUA AND MATHEMATICAL SCIENCES, 2025)
In this study, we introduce the Wrapping New XLindley Distribution (WNXLD) as an extension of the Wrapping Distribution (WD). We derive the probability density function, cumulative distribution function, characteristic function, trigonometric moments, and other relevant parameters for WNXLD Additionally, parameter estimation is performed using the maximum likelihood estimation method.
Keywords: Circular statistics; Compressive Strength; GGBS; Metakaoline; New Xlindley; Regression Analysis; Split Tensile Strength; Wrapping; Trigonometric moments.